Recent Trends in Bioinspired Metal Nanoparticles for Targeting Drug-Resistant Biofilms - Devaraj Bharathi; Jintae Lee (Pharmaceuticals, 2025)
Multidrug-resistant (MDR) biofilm infections characterized by densely packed microbial communities encased in protective extracellular matrices pose a formidable challenge to conventional antimicrobial therapies and are a major contributor to chronic, recurrent and device-associated infections. These biofilms significantly reduce antibiotic penetration, facilitate the survival of dormant persister cells and promote horizontal gene transfer, all of which contribute to the emergence and persistence of MDR pathogens. Metal nanoparticles (MNPs) have emerged as promising alternatives due to their potent antibiofilm properties. However, conventional synthesis methods are associated with high costs, complexity, inefficiency and negative environmental impacts. To overcome these limitations there has been a global push toward the development of sustainable and eco-friendly synthesis approaches. Recent advancements have demonstrated the successful use of various plant extracts, microbial cultures, and biomolecules for the green synthesis of MNPs, which offers biocompatibility, scalability, and environmental safety. This review provides a comprehensive overview of recent trends and the latest progress in the green synthesis of MNPs including silver (Ag), gold (Au), platinum (Pt), and selenium (Se), and also explores the mechanistic pathways and characterization techniques. Furthermore, it highlights the antibiofilm applications of these MNPs emphasizing their roles in disrupting biofilms and restoring the efficacy of existing antimicrobial strategies.